2010
DOI: 10.1029/2008wr007506
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a rainfall event threshold triggering herbicide leaching by preferential flow

Abstract: [1] How can leaching risk be assessed if the chemical flux and/or the toxicity is highly uncertain? For many strongly sorbing pesticides it is known that their transport through the unsaturated zone occurs intermittently through preferential flow, triggered by significant rainfall events. In these circumstances the timing and frequency of these rainfall events may allow quantification of leaching risk to overcome the limitations of flux prediction. In this paper we analyze the leaching behavior of bromide and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 36 publications
(53 reference statements)
4
35
0
Order By: Relevance
“…While numerous small precipitation events do not have significant influence on tile effluent Br concentration or tile flow rates during the 3 weeks following tracer application, relatively high intensity events on 21 and 27 November both induce temporary increases in Br concentration and tile flow and suggest a threshold for the initiation of preferential solute leaching (McGrath et al, 2010). The hydrologic response to the series of precipitation events during the latter part of November shows that in order for precipitation to notably influence tile effluent Br concentration, rainfall intensity needs to exceed approximately 2 mm h À1 , which is very close to K(w À5cm ) for the soil at the site (Table 2).…”
Section: Short Term Tracer Movement To the Tile Drainmentioning
confidence: 95%
“…While numerous small precipitation events do not have significant influence on tile effluent Br concentration or tile flow rates during the 3 weeks following tracer application, relatively high intensity events on 21 and 27 November both induce temporary increases in Br concentration and tile flow and suggest a threshold for the initiation of preferential solute leaching (McGrath et al, 2010). The hydrologic response to the series of precipitation events during the latter part of November shows that in order for precipitation to notably influence tile effluent Br concentration, rainfall intensity needs to exceed approximately 2 mm h À1 , which is very close to K(w À5cm ) for the soil at the site (Table 2).…”
Section: Short Term Tracer Movement To the Tile Drainmentioning
confidence: 95%
“…Several studies have demonstrated that macroporosity less than 0.1 % can be responsible for 70-85 % of water flux observed in fields (Watson and Luxmoore 1986;Wilson and Luxmoore 1988;Holden 2009a). Although increase in infiltration of rainfall through macropores reduces surface runoff and soil erosion, it can cause preferential flow and thereby transport fertilizers or other agricultural chemicals applied to surface soil to deep soil and even to groundwater (Allaire et al 2002;McGrath et al 2010). Preferential flow through surface soil also accelerates the generation of subsurface lateral flow over the impermeable deep soil and hence transports the chemicals to a long distance into streams (Wang et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Heavy rainfall immediately after pesticide application has also been identified by Lewan et al (2009) as a main control for pesticide leaching. This specific rainfall event was above a pesticide leaching threshold of 19 mm precipitation identified by McGrath et al (2010), and led to rapid preferential transport and leaching of TFMP. This threshold was identified from a lysimeter study using a silt loam soil.…”
Section: Fourth Applicationmentioning
confidence: 98%
“…It is therefore imperative to regulate use of FPB based on knowledge about FPB application (time and dose) on different crops so as to minimise the leaching potential of the highly soluble TFMP. Previous studies indicate that the timing of application in relation to precipitation events play an important role in leaching of pesticides (Kladivko et al, 2001;McGrath et al, 2010), as well as the magnitude of the precipitation event. This was also concluded by Brown and van Beinum (2009), which gave the time interval between application and the first major precipitation event a significant influence on pesticide leaching.…”
Section: Introductionmentioning
confidence: 99%